Urban growth threatens ancestral lands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
As cities expand to cover farmland with roads and buildings, the conflict between traditional land rights, and modern systems of ownership and distribution become very clear. This report comes from Blantyre in Malawi, where city authorities now charge rent on land that was once freely owned.